Tiger is a scaredy cat - Phillips, Joan.; Gorbaty, Norman (New York, NY : Random House, 1986)
Tiger, a scaredy cat who is even afraid of the mice in his house, conquers his fear to help Baby Mouse.
80
80
Accelerated Reader AR
Keywords: Courage -- Fiction; Cats -- Fiction; Mice -- Fiction